Trace fossils from the Upper Member of the Duolbagáisá Formation (Cambrian Series 2-Miaolingian), northern Norway, with the first diverse Cambrian record of Halimedides - Novis, Linn Kristin; Jensen, Sören; Høyberget, Magne; Högström, Anette (Norwegian Journal of Geology, 2022)
Source at https://njg.geologi.no/vol-101-200/details/30/2356-2356.html . New information is provided on trace fossils from the Cambrian Series 2 toNew information is provided on trace fossils from the Cambrian Series 2 toMiaolingian in the Upper Member of the Duolbagáisá Formation of northern Norway. This includes the first rich Cambrian material of Halimedides, a tracefossil with more or less regularly spaced swellings of different shapesconnected by a median string. It is known principally from Mesozoic andyounger deep-sea deposits, with a scarce Paleozoic record, making this one ofthe oldest occurrences of this ichnogenus. Other trace fossils occurring with Halimedides include the rare Bergaueria sucta, Palaeophycus imbricatus and Cruziana tenella. Psammichnites gigas and Syringomorpha nilssoni aredocumented photographically for the first time from this unit. The trace fossilassociation shows general similarity with that of the slightly older MickwitziaSandstone Member of southern Sweden and suggests a broad distribution oflate early Cambrian trace-fossil producers across Baltica.